SGLT2 inhibitors as metabolic modulators: beyond glycemic control in type 2 diabetes - Qian Wu; Jian Zhang; Fuli Zhang; Dongnan Li (Frontiers in Endocrinology)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder, and its management has evolved from mere glycemic control to multitarget metabolic regulation. Sodium–glucose cotransporter 2 inhibitors (SGLT2is) have demonstrated extensive pleiotropic effects in treating T2DM, and its complications through unique mechanisms. SGLT2is promote urinary glucose excretion, leading to a negative energy balance that triggers lipid metabolic reprogramming and fuel switching in the body. This process significantly reduces visceral fat deposition and improves insulin resistance and the inflammatory status. Additionally, SGLT2is provide a metabolic foundation for cardiovascular, hepatic, and renal protection through multiple pathways, including remodeling cardiac structure, enhancing myocardial metabolism, reducing uric acid levels, and alleviating renal hypoxia. With respect to combination therapy, the pairing of SGLT2is with other hypoglycemic agents and cardiovascular protective drugs has synergistic effects; however, potential adverse reactions should also be considered. Future research should investigate the precise application and long-term safety of SGLT2is as well as develop individualized treatment strategies on the basis of patients’ metabolic phenotypes, complications, and drug tolerability to maximize clinical benefits for patients. This review systematically explores the significant roles of SGLT2is in metabolic regulation, cardiovascular protection, and combination therapy, with the aim of providing a comprehensive foundation for optimizing individualized treatment strategies in T2DM management.